Brownfields do not "only live twice": The possibilities for heritage preservation and the enlargement of leisure time activities in Brno, the Czech Republic. (April 2018) - Navratil, Josef; Krejci, Tomas; Martinat, Stanislav; Pasqualetti, Martin J.; Klusacek, Petr; Frantal, Bohumil; Tochackova, Klara
Abstract: Central Europe is replete with legacy contaminated sites, commonly called "brownfields". The question is what can be done to remediate them and make them again safe and useful to society. This question is addressed in post-socialistic city of Brno, the Czech Republic. Our research assesses public perceptions of such sites that are currently utilized for the leisure time activities. Special attention is paid to public views of heritage preservation as an option for brownfield regeneration. The principal aim of the paper is to measure public support of heritage preservation through the conversion of brownfields to leisure activities and tourism. Data were gathered by means of the questionnaire survey with visitors of four brownfields currently being used for leisure time activities (n = 130). It was revealed that the awareness of the visitors of the issue of brownfield regeneration is very low, and that importantly affects the perception of heritage preservation of individual sites. Further, the opinions of the respondents are significantly influenced by the local contexts of individual brownfields (predominantly by the situation and the technical state). However, it might be stated that in locations where the historical state of building has already been repaired, historical heritage is perceived more positively. Highlights: Public support of heritage preservation is measured through the conversion of brownfields to leisure activities and tourism. The awareness of the visitors of the issue of brownfield regeneration is very low. The opinions of the respondents are significantly influenced by the local contexts of individual brownfields. In locations where the historical state of buildings has been repaired, historical heritage is perceived more positively.